2020
DOI: 10.1080/09644008.2020.1786058
|View full text |Cite
|
Sign up to set email alerts
|

Deliberating Foreign Policy: Perceptions and Effects of Citizen Participation in Germany

Abstract: Citizen participation has been a popular format in policy fields like environmental and climate policies for many years. More recently, however, it has extended to issues of foreign policy, which has long been considered as a prerogative of the executive in democratic systems. This paper analyses citizen participation in German foreign policy by comparing deliberative-participatory processes implemented by the German Federal Foreign Office (AA) and the Ministry for the Environment, Nature Conservation, and Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Digital engagement tools not only enable the submission of feedback and proposals from the public; they also facilitate greater transparency in the decisionmaking process itself. When citizens can observe and contribute to policy formulation in virtual environments, it engenders a more democratic form of governance where decisions are a reflection of wide-ranging citizen input (C. Oliveira, 2019;Pfeifer et al, 2021). The construction and adoption of policies become more than a statutory requirement; they transform into a shared venture between government and governed.…”
Section: Prospects For Open Government In Vietnammentioning
confidence: 99%
“…Digital engagement tools not only enable the submission of feedback and proposals from the public; they also facilitate greater transparency in the decisionmaking process itself. When citizens can observe and contribute to policy formulation in virtual environments, it engenders a more democratic form of governance where decisions are a reflection of wide-ranging citizen input (C. Oliveira, 2019;Pfeifer et al, 2021). The construction and adoption of policies become more than a statutory requirement; they transform into a shared venture between government and governed.…”
Section: Prospects For Open Government In Vietnammentioning
confidence: 99%
“…Moreover, policymakers from different policy areas may hold different attitudes. Comparing the practices for citizen participation in foreign policy and environmental policy in Germany, Pfeifer et al (2021) found the latter to be a more fruitful setting for citizen involvement. Using interviews, participant observations and official documents, the authors concluded that while foreign policy may require the kind of expertise that citizens seldom can possess, they are typically much better equipped to handle environmental issues.…”
Section: Attitudes Towards Citizen Engagementmentioning
confidence: 99%
“…Furthermore, political parties can serve as conduits for gathering public preferences and turning deliberative decisions into policy recommendations. By pushing for the inclusion of deliberative results in policy-making processes, they help bridge the gap between public deliberation and policy implementation (Pfeifer et al, 2021).…”
Section: Challenges and Opportunities For Political Parties Under Del...mentioning
confidence: 99%